A DESCRIPTIVE STUDY OF CODE MIXING FORM IN KASKUS ONLINE FORUM - Aga Hamengku Budi; Fadly Azhar; Dahnilsyah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research objective is to find out the form of code mixing in Kaskus online forum. The research data were collected in february 2017. The subject of this research was the user of Kaskus online forum in a thread entitiles “Cara Asik to Improve Your English”. The data were collected through online report. The subject consisted of 16 users with 48 posts, and 64 sentences. The research found out that the all of code mixing forms exist in Kaskus and several purposes of code mixing are found in this research. As a conclusion, the use of insertion of words is more dominant than other insertion in the research and Kaskus users are not using the code mixing for their incompetence.Keywords: Sociolinguistic, Code Mixing